A bcc refractory high-entropy alloy: the ideal case of smooth plastic flow - Yen-Ting Chang; Abhi Sharda; Julian M. Rosalie; Robert Maaß; Marie A. Charpagne (Materials Research Letters)
Single crystalline metals exhibit correlated dislocation dynamics, irrespective of lattice system. This collective evolution of dislocation structures is intermittent and scale-free, implying divergent length scales that play a critical role in failure initiation and therefore microstructural design. Here we report on a HfNbTaTiZr refractory high-entropy alloy, that lacks criticality in the collective dislocation response. This unusual behaviour manifests itself in almost quenched-out microplastic stress-strain fluctuations and sluggish dislocation avalanching, otherwise only seen in complex engineering alloys. These findings demonstrate how the high-entropy paradigm can serve as a role model to effectively suppress unwanted plastic fluctuations in metals deformation.